Program Pelatihan Peningkatan Kompetensi Guru Sekolah Dasar Luar Biasa - Situmorang, Marline; Ahmad, Masduki; Zulaikha, Siti (Publikasi Pendidikan, 2024)
Quality education will require qualified teachers who have potential and ability to improve the quality of education in schools. The main objective of this research is to evaluate teacher training toward teacher development as a professional teacher. This research uses qualitative approach and involves principal and teachers as the main subjects. Collecting data through observation, interviews, and document analysis then analyzing by qualitative descriptive analysis. The results show that training and development give best impact on teacher performance, improving quality and value of the teachers.Keywords: teacher competency, teacher training, elementary school